The Cream of the Crop? Geography, Networks, and Irish Migrant Selection in the Age of Mass Migration. (14th March 2019) - Connor, Dylan Shane
Abstract : With more than 30 million people moving to North America during the Age of Mass Migration (1850–1913), governments feared that Europe was losing its most talented workers. Using new data from Ireland in the early twentieth century, I provide evidence to the contrary, showing that the sons of farmers and illiterate men were more likely to emigrate than their literate and skilled counterparts. Emigration rates were highest in poorer farming communities with stronger migrant networks. I constructed these data using new name-based techniques to follow people over time and to measure chain migration from origin communities to the United States.